Induksi Pertumbuhan Tunas Tanaman Manggis (Garcinia mangostana L.) Secara In Vitro - Asri, Elita; Harahap, Fauziyah; Hasairin, Ashar (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
This study aims to determine the effect of plant growth regulators and seed cutting patterns on the induction of mangosteen shoot growth. The research was conducted at the YAHDI Tissue Culture Laboratory in Medan, North Sumatra, Indonesia, in 20245. The method used in this study was a Completely Randomized Design (CRD) with two factors: BAP concentration and seed cutting pattern. The data collected were analyzed using statistical analysis of variance (ANOVA) with Duncan's Multiple Range Test (DMRT) at a 5% significance level using SPSS 26. The results of the study show that the interaction between BAP concentration and seed cutting pattern significantly affected the time of shoot emergence, the number of leaves, and the shoot height. The best shoot emergence time was obtained with a BAP treatment of 4 mg/L using whole seed explants, which occurred at 1 MST (Month After Sowing). A BAP concentration of 2 mg/L with whole seed explants produced the highest number of leaves, with 8 leaves. The highest number of shoots was obtained from explants planted in a medium with 6 mg/L BAP, which resulted in 5.67 shoots. Whole seeds planted in a medium with 0 mg/L BAP produced the tallest plants, measuring 8.9 cm. The combination of BAP concentration and seed cutting pattern did not significantly affect the number of roots.